Dimensions for Scoping e-Government Enterprise Architecture Development Efforts - Nakakawa, Agnes; Namagembe, Flavia; Proper, Erik H. A. (Springer International Publishing, 2018)
Inspired by developed economies, many developing economies are adopting an enterprise architecture approach to e-government implementation in order to overcome challenges of e-government interoperability. However, when developing an enterprise architecture for a complex enterprise such as the egovernment enterprise, there is need to rationally specify scope dimensions. Addressing this requires guidance from e-government maturity models that provide insights into phasing e-government implementations; and enterprise architecture approaches that provide general insight into key dimensions for scoping enterprise architecture efforts. Although such insights exist, there is hardly detailed guidance on scoping initiatives associated with developing an egovernment enterprise architecture. Yet the success of such business-IT alignment initiatives is often affected by scope issues. Thus, this paper presents an intertwined procedure that draws insights from e-government maturity models and enterprise architecture frameworks to specify critical aspects in scoping egovernment enterprise architecture development efforts. The procedure was validated using a field demo conducted in a Uganda public entity.
Keywords: e-Government maturity; e-Government enterprise architectures